Root cause analysis of a failure in a flange-pipe welded joint in a steam line in an ammonia plant: Experimental investigation and simulation assessment. (November 2021) - Taghipour, M.; Bahrami, A.; Mohammadi, H.; Esmaeili, V.
Highlights: Failure of a flange-pipe welded joint is investigated. Poor welding design containing sharp corners is observed. At the root region, coarse microstructure with poor strength is seen. The distribution of residual stress is computed around the joint. The correlations between the results and observed failure are discussed. Abstract: This study aims to investigate the root cause of a failure in an ASTM A106 pipe-ASTM A105 flange welded joint, welded to a pump in an ammonia plant. Samples were taken from the failed joint. These joints were exposed to steam at the temperature of 148 °C and internal pressure of 7 bar. The changes in metal microstructures along the welded metal showed that root pass region consists of large grain-size structure, containing Widmanstätten, grain boundary and polygonal ferrite structures. On the other hand, the areas on the middle and upper sections of the weld mostly contained acicular ferrites. The results of hardness tests indicated that the root pass region has lower hardness compared to other areas which is due to large grain size structure in this region. In addition, simulation results showed that a rather large residual tensile stress exists at the root of the weldment. Besides, results of fractography showed that areas close to the weld root consisted of a quasi-cleavage structure. Based on the results, it can be postulated that the main reason for the failure was unsuitable welding parameters which have resulted in the formation of large grain structures with low strength.